Forming the Character of a Physically Healthy Young Generation Through Military Education - Yoki Muchsam; Bambang Sucipto; Rismawati Rismawati; Imanita Septian Rusdianti; Agung Rachmat Raharja (TGO Journal of Community Development, 2023)
This activity aims to develop the character of the young generation with good physical health through military education at Dodik Belanegara Rindam III Siliwangi, West Bandung. The methods applied include the preparation and implementation of the program, involving the entire academic community. The evaluation results show that the activity went smoothly, and the participants successfully achieved the set goals, showing improvements in physical health and character strengthening through discipline and teamwork. The discussion covers the program's success, involvement of all parties, and benefits felt by the participants. Limitations in logistics and the need for more in-depth evaluation are identified as areas for improvement. Meanwhile, suggestions for further development include the application of comprehensive evaluation methods, increased inter-institutional collaboration, and the development of a more contextual curriculum. Key findings from this study include the program's success in shaping the character and health of the younger generation, highlighting the importance of military education as a means of holistic character formation at the higher education level. These findings provide a basis for the development of similar programs in the future, with a focus on the necessary improvements to enhance their positive impact.